Obstetrical and perinatal outcomes of women with preeclampsia at Woldia Comprehensive Specialized Hospital, Northeast Ethiopia - Kumsa, Henok; Mergiyaw, Desalew (Frontiers in Medicine, 2024)
Background: Preeclampsia is a multisystem disorder that affects pregnant women.Preeclampsia and its complications are leading causes of maternal and perinatal morbidity and mortality in developing countries. Studies conducted in Ethiopia have primarily concentrated on preeclampsia's trends and prevalence rather than its obstetrical and perinatal consequences.Thus, this study aims to determine the risk of adverse obstetric and perinatal outcomes among women with preeclampsia at Woldia Comprehensive Specialized Hospital, Northeast Ethiopia.Methods: A retrospective cohort study was done among 140 preeclamptic women and 280 normotensive women who gave birth at Woldia Comprehensive Specialized Hospital between December 30, 2020, and December 29, 2022. Maternal records were retrieved using dataextraction tools. The data were entered into Epi-data version 4.6.0.6 and analyzed using SPSS version 26. Binary and multivariable logistic regression models were used to test the associations between independent and outcome variables. The adjusted odds ratio (OR) with a 95% confidence interval (CI) and p-values <0.05, were used to measure the strength of the association and declare the level of statistical significance.The odds of at least one adverse obstetric outcome among preeclamptic women was 2.25 times higher as that among normotensive women [AOR: 2.25, 95% CI: (1.06, 4.77)]. In addition, babies born from preeclamptic women were a higher risk of perinatal death [AOR: 2.90, 95% CI: (1.10, 8.17)], low birth weight [AOR: 3.11, 95% CI: (1.43, 6.7)], birth asphyxia [AOR: 2.53, 95% CI: (1.15, 5.5)], and preterm birth [AOR: 2.21, 95% CI: (1.02, 4.8)] than babies born to normotensive women.Conclusions: More adverse obstetric and perinatal outcomes were observed in women with preeclampsia than those in normotensive women. This study highlights the significantly elevated level of at least one adverse obstetric outcome associated with preeclampsia, low hemoglobin level, and rural residents. Moreover, perinatal death, low birth weight, asphyxia, and preterm birth were significantly associated with preeclampsia.